Neuro-adaptive process control a practical approach - Mills, Peter M. (John Wiley & Sons, 1996)
Using a series of rigorous authentic examples, the authors demonstrate several simple yet practical techniques for utilizing adaptive neural networks to produce more efficient process control. Their in-depth description of implementation issues offers a wealth of pragmatic wisdom.